Time to reform the US federal agricultural insurance program - Smith, Vincent H.; Glauber, Joseph W.; Goodwin, Barry K. (American Enterprise Institute, 2017)
In the past few decades, the federal crop insurance program has become a major source of subsidies for farmers, with more than 300 million acres and 130 crops enrolled in the program. Although a number of other programs faced budget cuts in the 2014 Farm Bill, legislators protected subsidies for the federal crop insurance program from any cuts and expanded the scope of the program. The total cost of the federal crop insurance program is likely to average about $8 billion a year over the next 10 years, of which on average about $5.5 billion a year will flow to farmers, enhancing their incomes, and $2.5 billion will flow to private crop insurance companies and agents. In addition to being expensive, the federal crop insurance also encourages farmers to waste resources, is disproportionately targeted to large and successful farm operations that have no need of federal assistance, and has the potential to engage the US in World Trade Organization disputes with other countries over the trade impacts of US agricultural policy. In light of these problems, some experts argue that the federal crop insurance program should be eliminated, although this option is unlikely to be popular with farmers, insurance companies, and farm state legislators. A viable alternative is to replace the entire crop insurance program with a “no cost to farmers” disaster aid program based on indexes of plant growth constructed for each covered crop. If the crop insurance program is continued, at the very least, as some legislators and successive administrations have proposed, a costly and heavily subsidized endorsement called the Harvest Price Option should be terminated, with a potential savings in taxpayer outlays of close to $2 billion. Other changes, such as farm level caps on premium subsidies, reductions in premium subsidy rates, and introducing price competition among insurance companies should also be considered.